Mapping Paintings - Boston University; Samuel H. Kress Foundation (2017)
[Engl.:] Mapping Paintings is an open-source platform that allows users to tailor-make their own individual scholarly mapping projects. Users can make their projects private or public. The uploaded data, once approved by our admin team, becomes part of the global library, which is available to all users of the site.